2020
DOI: 10.1080/02692171.2020.1749241
|View full text |Cite
|
Sign up to set email alerts
|

Riding the storm: fiscal sustainability in the Caribbean

Abstract: Fiscal sustainability remains a paramount challenge for small economies with high debt and greater vulnerability to climate change. This paper applies the model-based sustainability test for fiscal policy in a panel of 16 Caribbean countries during the period 1980-2018. The results indicate that the coefficient on lagged government debt is positive and statistically significant, implying that fiscal policy in the Caribbean takes corrective actions to counteract an increase in the debt-to-GDP ratio. Nonlinear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
4
18
1
Order By: Relevance
“…Second, the coefficient on (lagged) government debt is also found to have a significant negative sign, which means that there is no positive response in the CAPB to changes in the debt-to-GDP ratio and therefore the necessary condition of fiscal sustainability was not met during the sample period. These findings are in line with the literature showing that developing countries tend to exhibit procyclicality in fiscal policy (Gavin and Perotti, 1997;Talvi and Vegh, 2005;Alesina, Campante, and Tabellini, 2008;Iletzki and Vegh, 2008;Cevik and Teksoz, 2014), but contradictory with the cross-country analysis of Caribbean countries that are found to maintain a countercyclical fiscal stance and take corrective actions against an increase in the debt-to-GDP ratio (Cevik and Nanda, 2019). However, it should be noted that there has been a significant shift in Belize's fiscal effort over the past two years following the latest debt restructuring (similar to previous episodes in 2007 and 2013), as indicated by a larger coefficient (in absolute value) on the debt variable when the model is estimated for the period until 2016.…”
Section: Table 1 Fiscal Reaction Function Estimates For Belizesupporting
confidence: 84%
“…Second, the coefficient on (lagged) government debt is also found to have a significant negative sign, which means that there is no positive response in the CAPB to changes in the debt-to-GDP ratio and therefore the necessary condition of fiscal sustainability was not met during the sample period. These findings are in line with the literature showing that developing countries tend to exhibit procyclicality in fiscal policy (Gavin and Perotti, 1997;Talvi and Vegh, 2005;Alesina, Campante, and Tabellini, 2008;Iletzki and Vegh, 2008;Cevik and Teksoz, 2014), but contradictory with the cross-country analysis of Caribbean countries that are found to maintain a countercyclical fiscal stance and take corrective actions against an increase in the debt-to-GDP ratio (Cevik and Nanda, 2019). However, it should be noted that there has been a significant shift in Belize's fiscal effort over the past two years following the latest debt restructuring (similar to previous episodes in 2007 and 2013), as indicated by a larger coefficient (in absolute value) on the debt variable when the model is estimated for the period until 2016.…”
Section: Table 1 Fiscal Reaction Function Estimates For Belizesupporting
confidence: 84%
“…However, a higher debt ratio raises interest payments, causing the fiscal balance to deteriorate (Tujula and Wolswijk, 2004). Melitz (2000), Ghosh et al (2013) and Cevik and Nanda (2020) have suggested a quadratic formulation, but we find an insignificant estimated coefficient of the quadratic term.…”
Section: Control Variablescontrasting
confidence: 67%
“…To the best of our knowledge, so far, there is no study exploring the effects of climate change on debt and public finances in the MENA region. Studies have documented budgetary and debt effects of climate change in the USA, Europe, Latin America and the Caribbean (LAC) countries (Lis and Nickel, 2010;Acevedo Mejia, 2014Cevik and Nanda, 2020;Congressional Budget Office, 2021). Our findings show a significant temperature impact on fiscal balance and the debt-to-GDP ratio, but we report no rainfall effect.…”
Section: Introductionmentioning
confidence: 99%
“…Cevik and Nanda (2020) have tried to evaluate the sustainability of Caribbean fiscal deficits using data sets for the period 1980 to 2018 applying FRF develop by Bohn (2005). The study reveals that the governments have tried to design their policies keeping the sustainability considerations to counteract an increase in the debt-to-GDP ratio.…”
Section: Fiscal Sustainability: Methodologies and Empirical Evidencementioning
confidence: 99%